English Teacher’s Motivation to Achieve Professional Teacher - Husna, Noviyanti Nurul; Arrasyid, Farouk Imam; Nashruddin, Wakhid (Department of English Language Education, UIN Sunan Ampel Surabaya, 2025)
Teacher professionalism is a value, purpose, and quality of expertise related to the work of a teacher. Professional teachers possess the talent, interest, motivation, competence, and responsibility to perform their job effectively. The purpose of this research is to investigate the impact of teachers' motivation on their professionalism. The research method employed is qualitative research, utilizing a case study approach. The instruments used were observation, interview, and a documentation study. The informants in this study were three English teachers at SMKN 1 Cirebon. The research results showed that becoming a professional English teacher requires several efforts. First, teachers must possess talent, interest, and motivation. Second, teachers must also have an educational background that aligns with their field. Third, teachers must have the competencies required by their field of work. Lastly, teachers must take responsibility for carrying out their duties as teachers.